Remote trajectory programming with sensory feedback for an exoskeleton - Guillermo, Sanchez Palomino Jose; Escarcina, Raquel Esperanza Patiño (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XXI Simpósio Latino Americano de Robótica, 2024)
In the area of physical medicine and rehabilitation, there is a problem when performing the exercise routines proposed by physiotherapists, since they do not have statistics and history on the rehabilitation process of each patient. Therefore, programmable routines are performed on the Poppy humanoid robot, identifying the position and speed of each movement. Neck and arm movements are performed according to the angles allowed in the Poppy robot, having a 98% effectiveness on each routine.